1996
DOI: 10.1111/j.1349-7006.1996.tb03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of CD44 Variants in Differentiated Thyroid Cancers

Abstract: Expression of CD44 variants in thyroid tumors was analyzed by reverse transcription‐polymerase chain reaction (RT‐PCR) with a fluorescent image analyzer. Increased expression of CD44 variants compared with normal thyroid tissues was observed in most thyroid follicular tumors, especially in follicular carcinomas, poorly differentiated papillary carcinomas and some follicular adenomas. However, variants were hardly detectable in an anaplastic carcinoma. Analysis with restriction enzymes revealed that the major P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We previously reported that a specific CD44 splice variant, CD44v8-10, which contains variant exons 8, 9, and 10 (also referred to as CD44R1) is highly expressed in colon carcinomas compared with adjacent nonneoplastic tissues (44). Since we reported this finding, other groups have also described the predominant expression of CD44v8-10 in various human carcinomas, including breast (34), gastric (41), and thyroid (45). To analyze CD44v8-10 expression further, in this study we examined the CD44 splice variants expressed in non-small-cell lung carcinomas (NSCLCs) and bladder carcinomas and confirmed that CD44v8-10 was the most dominant splice variant in these tumor tissues.…”
supporting
confidence: 63%
“…We previously reported that a specific CD44 splice variant, CD44v8-10, which contains variant exons 8, 9, and 10 (also referred to as CD44R1) is highly expressed in colon carcinomas compared with adjacent nonneoplastic tissues (44). Since we reported this finding, other groups have also described the predominant expression of CD44v8-10 in various human carcinomas, including breast (34), gastric (41), and thyroid (45). To analyze CD44v8-10 expression further, in this study we examined the CD44 splice variants expressed in non-small-cell lung carcinomas (NSCLCs) and bladder carcinomas and confirmed that CD44v8-10 was the most dominant splice variant in these tumor tissues.…”
supporting
confidence: 63%
“…Among the overexpressed genes, many are known from previous studies to be involved in PTC. A prototype example is FN1 (fibronectin 1), which is highly overexpressed in PTC (11). Other examples include MET (12), DPP4 (dipeptidylpeptidase IV) (13), SER-PINA1 (␣ 1-antitrypsin) (14), KRT19 (keratin 19) (15), and LGALS3 (galectin-3) (16), which were overexpressed in all eight PTC samples.…”
Section: Resultsmentioning
confidence: 99%
“…The study also showed increased expression of CD44 variants compared with normal thyroid tissues in FTC, PTC, and some follicular adenomas 52. It is believed that the expression of CD44v3 and CD44v6 variant isoforms might be crucial in the development of nodal metastasis in cases of FTC 53.…”
Section: The Biomarkers For Tmn Oncolytic Virotherapymentioning
confidence: 65%
“… 51 The study also showed increased expression of CD44 variants compared with normal thyroid tissues in FTC, PTC, and some follicular adenomas. 52 It is believed that the expression of CD44v3 and CD44v6 variant isoforms might be crucial in the development of nodal metastasis in cases of FTC. 53 CD44 was detected with an antibody recognizing all forms of CD44, including CD44v3 and CD44v6 variant isoforms, in 213 patients with DTC.…”
Section: The Biomarkers For Tmn Oncolytic Virotherapymentioning
confidence: 99%